HISTORICAL EXTREME TEMPERATURE TRENDS IN A PART OF SUB-SAHARAN AFRICA - Idowu,; Adefunke, Mary (Malaysian Journal of Tropical Geography (MJTG), 2023)
The study examines the historical trends and changes in extreme temperature events in Nigeria using both observed (NIIMET) and simulated (Regional Climate Model) data over the study area. The spatiotemporal patterns, variability and trend analysis of the datasets were carried out. Fourteen (14) indices of the 27 climate indices were used to determine the trends and changes in extreme events across the region. Results showed an increase in trends of minimum and maximum temperature across the eco-climatic regions of Nigeria, and the RegCM replicated the observed data for most of the eco-climatic regions, except for the Sudan savanna. The study identified significant implications attributed to the temperature increase in humans, plants and animals.